Rock physics model for deep coal-bed methane reservoir based on equivalent medium theory: A case study of Carboniferous-Permian in Eastern Ordos Basin - Zhang Bing; Zhang Haifeng; Pan Fuyou (Open Geosciences)
The deep coal-bed methane (CBM) resources represented by the Benxi Formation in the Eastern Ordos Basin have enormous potential and have achieved industrial breakthroughs in recent years. Rock physics modeling is a key research topic for predicting deep CBM reservoirs, but the relationship between parameters such as vitrinite reflectance (Ro), coal rock composition, total gas content, ash content, porosity, and elastic parameters is not clear, necessitating further research on rock physics models suitable for deep CBM reservoirs. On the basis of optimizing the skeleton parameters of the coal matrix (ash content, coal rock type), the porosity parameters of CBM reservoirs are obtained by using the nuclear magnetic resonance method. Equivalent calculation of adsorbed gas and total gas content using adsorbed gas as part of the coal matrix. Based on the measured data, calculate the pore fluid, temperature, and pressure data by taking the average or predicting the curve. Considering the geological characteristics and relevant background of deep CBM reservoirs in the Eastern Ordos Basin, a seismic rock physics model of hydrocarbon reservoirs considering the influence of CBM reservoirs was constructed. The specific process involves using coal matrix + adsorbed gas + matrix pores + cleat (or crack) pores as the dry skeleton, filling with water + free gas as the fluid, and using anisotropic rock physics modeling ideas to complete saturated coal rock physics modeling. By comparing the predicted longitudinal and transverse wave curves with actual measurements, the trends of the two are basically consistent, with a relative error of less than 1%, indicating that the model parameters are reasonably selected.